Wu-Mei-Wan Ameliorates Murine Ulcerative Colitis by Regulating Macrophage Polarization - Yan, Shuguang; Wei, Hailiang; Jia, Rui; Zhen, Meijia; Bao, Shengchuan; Wang, Wenba; Liu, Fanrong; Li, Jingtao (Frontiers in Pharmacology, 2022)
An increasing body of evidence shows that macrophages play an important role in the pathogenesis of Ulcerative colitis (UC). Macrophage polarization and changes in related signaling pathways are reported to have a protective effect on intestinal inflammation. The well-known Chinese medicine Wumeiwan (WMW) has been used to treat diarrhea, one of the main symptoms of colitis, for more than 2,000 years. Increasing evidence shows that WMW can inhibit intestinal inflammation and repair damaged intestinal mucosa, but its effector mechanisms are unknown. Therefore, we studied the prophylactic effects of WMW in dextran sulfate sodium (DSS)-induced UC and its effects on macrophage mechanisms and polarization. The results show that colitis was significantly alleviated in mice in the WMW group, the secretion and expression of pro-inflammatory factors TNF-α, IL-1ꞵ, and IL-6 were inhibited in the serum and colonic tissues of mice with WMW-treated colitis, whereas anti-inflammatory factors IL-10, Arg-1, and TGF-β1 were increased. Subsequent studies found that WMW could inhibit M1 polarization and promote M2 polarization in colonic macrophages in DSS-induced colitis mice. Network pharmacology was used to predict potential targets and pathways. and further studies confirmed the related targets The results showed WMW gradually inhibits the activation of the P38MAPK and NF-κB signaling pathways and further activates the STAT6 signaling pathway. In summary, WMW interferes with the p38MAPK, NF-κB and STAT6 signaling pathways to regulate M1/M2 polarization in macrophages, thereby protecting mice against DSS-induced colitis.